Pesantren Virtual: Dinamisasi atau Disrupsi Pesantren? - Hatta Fakhrurrozi (Paedagogia: Jurnal Pendidikan, 2021)
The industrial revolution that penetrated the world of education forced Islamic boarding schools (Pesantren), as part of education, to mutate in new form to find the ideal format as an adaptive step to keep up to date. Pesantren which have a cultural base of traditional society make various efforts to make acculturation with technology. The efforts of these pesantren can be seen from the number of pesantren websites, which provide information about pesantren and religious programs online. On the other hand, virtual pesantren have also emerged, which do not have a real pesantren institutional base in the community, using online media as an operational base. Some of these virtual Islamic boarding schools have strong buildings in cyberspace, with a wider reach than Islamic boarding schools. Its flexible and open nature makes virtual pesantren have their own community in cyberspace. Furthermore, problems arise when virtual Islamic boarding schools intersect with conventional Pesantren in cyberspace. This research is a library research that uses printed and online media as data sources. This study aims to find differences in the characteristics of virtual pesantren, and their relationship with the dynamics of pesantren in the era 4.0. From the content analysis conducted at several virtual pesantren, it was found that some of them used the same name as real pesantren, thus creating ambiguity of virtual pesantren